Current status and future prospects of research and development operations in traditional and complementary and alternative medicine manufacturing small- and medium-sized enterprises: a 2014 company-based survey - Miyoung Ahn; Eun-Ji Park; Jong-Min Woo (Integrative Medicine Research)
Background: Small- and medium-sized enterprises (SMEs) have played key roles in the economic growth and technical innovation of traditional and complementary and alternative medicine (T&CM). Research and development (R&D) are critical activities for industrial progress. This study aimed to characterize the current status of SME R&D activities and to explore manufacturersâ perceptions of R&D expansion. Methods: Records of the distribution of T&CM SMEs and R&D resources detailed in the 2014 Statistics of Korea T&CM Industries survey, a previously conducted survey on the industrial status of the T&CM field, were reviewed. Data on the perceptions of R&D activities were investigated through a company-based survey covering 285 T&CM-manufacturing SMEs. Results: Greater than 99% of the 13,636 T&CM manufacturers at the time of the study were SMEs employing less than 50 workers. Natural cosmetics manufacturing SMEs (NC SMEs) had the highest R&D expenditures. NC SMEs rely heavily on internal R&D operations, which may contribute to their strong need for R&D collaboration with public research institutions and expanded T&CM-promoted R&D programs. âDigestive system disordersâ are the main target diseases for current herbal and dietary supplement manufacturing SMEs and herbal medicine manufacturing SMEs. These SMEs tend to view their own product-related business as a priority for future R&D investment. Conclusion: This study represents the first attempt to assess SME perceptions of R&D activities. The findings herein can inform the design of sustainable programs that support R&D by reducing the gaps between the perspectives of T&CM product makers and policymakers. Keywords: R&D, SME, South Korea, survey, T&CM